Theoretical Analysis Of Educational Structures Of Conceptual Lines, Educational Elements And Logical Information Modeling In The Creation Of Digital Educational Resources (Eurasian Scientific Herald, 2022)
This article discusses the theoretical analysis of the theoretical analysis of educational structures of conceptual lines, educational elements and logical information modeling in the creation of digital educational resources. In addition, the theoretical analysis of the difference between the concepts “content of education” and “content of educational science (subject of study)” was made in didactics.